The Practices of Indonesia’s Cultural Diplomacy in Saudi Arabia through the Tourism Promotion Programs (2015-2018) - Putri, Annisa Dwida Sunggowo; Raharyo, Anggara; Hikam, Muhammad AS (Indonesian Perspective, 2021)
This article investigates Indonesia’s cultural diplomacy in Saudi Arabia through the tourism promotion programs from 2015 to 2018. Cultural diplomacy is aimed to raise awareness about the wealth of Indonesian culture relating to tourism that can be utilized in obtaining the desired outcomes. This article employs the concept of ‘sof power’ and qualitative approach with the technique of data collection by analysing the official documents from the Indonesian Ministry of Tourism, as well as the technique of secondary data collection that analyzes several literatures including books, reports, journals, and related articles. This article argues that Indonesia’s efforts in conducting cultural diplomacy practices in Saudi Arabia through the tourism promotion programs from 2015 to 2018 is involving the cultural elements to the programs that were Islamic-nuanced and recognized as the world’s intangible cultural heritage by the UNESCO.